Quartel Live Crisis In Students And Causative Factors - Harmelia Tulak; Alexander Pakiding; Adelia Adelia (Edumaspul: Jurnal Pendidikan, 2024)
Student's reactions to the adult phase can be diverse. The sheer number of choices that come from the external environment and the complexity of choosing the best one often create pressure. The purpose of this study is to determine the quarter-life crisis (QLC) in final-year students at UKI Toraja and reveal the factors that trigger the emergence of the condition. This research is descriptive and quantitative. The subjects of his research were final year students starting from semester 6 which amounted to 99 people. The results showed that the categorization of Quarter Life Crisis in final year students of UKI Toraja, is as follows: as many as 15 (15.15%) students fall into the high category, 82 (82.83%) students fall into the medium category, and 2 (2.02%) are in the low category. Through the calculation of the average score of each aspect of measurement achievement, the factors causing QLC were identified sequentially from the highest to the lowest aspects, namely aspect 7 (disconnection), aspect 3 (feeling anxious), aspect 1 (anxiety in making decisions), aspect 5 (negative self-assessment), aspect 6 (being stuck in a difficult situation), aspect 4 (depressed), and aspect 2 (worrying in interpersonal relationships).